Techno-Economic Analysis of a Wind-Energy-Based Charging Station for Electric Vehicles in High-Rise Buildings in Malaysia - Abdelrahim M.; Alkawsi G.; Alkahtani A.A.; Alhasan A.M.W.; Khudari M.; Abdul Kadir M.R.; Ekanayake J.; Tiong S.K. (MDPI, 2023)
Carbon dioxide; Charging (batteries); Economic analysis; Fossil fuels; Gas emissions; Global warming; Greenhouse gases; Laws and legislation; Tall buildings; Wind turbines; Charging station; Energy source; Energy-based; Financial evaluation; High rise building; Malaysia; Small scale; Small-scale turbine; Techno-Economic analysis; Techno-financial evaluation; Wind power